Gender differences in attributions about microcomputer learning in elementary school. - D'Amico, Miranda; Baron, Lois J.; Sissons, Mary Elizabeth (Sex Roles, 1995)
To investigate whether girls' attributions about computer use were more likely to follow a pattern of learned helplessness, boys' and girls' attributions about a computerized drill-and-practice task and a tutorial program were assessed. Factor analysis of responses on an attribution questionnaire revealed three factors that differed across gender and across task. Multiple regression, using exposure time, group size, attributions, and interactions to predict posttest scores, showed different patterns for boys and girls and between tasks. For the drill-and-practice task, girls benefited from increased exposure time, and attributions to ease of task and ability predicted performance for both boys and girls. For the tutorial task, increased exposure time did not benefit either sex. Girls, however, benefitted from working in larger groups, while boys benefitted from working in smaller groups. Attributions to luck, as well as perceptions of ability and ease of task, predicted posttest scores. However, for girls, attributions to luck predicted higher scores, while for boys, attributions to luck were negatively correlated with performance. Implications for including appropriate feedback to encourage a mastery approach in computer learning, as well as optimal group size and group composition for positive attributional style and academic success, are discussed. Reprinted by permission of the author.